EFEKTIVITAS PERENDAMAN TERHADAP NILAI KEKUATAN UYUNG SAGU (Metroxylon sagu) ASAL PULAU PADANG BERDASARKAN KARAKTER SERAT - Tiara Maulidza Riyani; Fitmawati '; Dyah Iriani (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Padang island is one of the islands that has the high Sago germplasm (Metroxylon sagu) in Kepulauan Meranti, Riau Province. This region has abundant sago bark waste called sago uyung but it has not been used properly. Sago uyung potentially produce a strong and termite resistant wood that can be used as handcraft raw material. This study aimed to analyze the effectiveness of wood soaking in three water types to the strength of uyung spined-sago of Padang island based on fiber characters. The uyungs of spined-sago were collected from three different habitats of sago, i.e. peat habitat, transition zone of peat and clay habitat as well as clay habitat, and treated in three water types, i.e. peat, sea and fresh water. The measurement and observation of fiber characters used a maseration method. This result showed that based on the treatments, uyung that soaked on the sea water gave the best result due to the longest and widest fiber. Moreover, based on the types of habitat, uyung from the transition zone of peat and clay habitat had the longest and widest fiber. The interaction of uyung from the transition zone of peat and clay habitat with sea water soaking was more effective in producing a strong sago uyung.